2017
DOI: 10.1108/jfep-02-2016-0013
|View full text |Cite
|
Sign up to set email alerts
|

Savings-investment-financial development trilogy: evidence from SSA

Abstract: Purpose The study seeks to examine the role of financial development (FD) in the Feldstein–Horioka (FH) puzzle. The novelty of this study is based on the fact that the measures of FD are expanded to account for the qualitative nature of the financial sector (“better finance”). Design/methodology/approach The study used annual dataset for 37 countries in sub-Saharan Africa (SSA) for the period 1999 through 2010 and relied on the system generalised method of moments (GMM) technique, which takes accounts of end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…First, as suggested by Ndikumana (2003), it is better to think in terms of banks and stock market rather than bank vs stock market because both types of indicators affect the level of domestic investment. Second in line with the findings of Raheem and Oyinlola (2017) and Iheonu et al (2020), as the efficiency-based, bank-based and market-based, financial development indicator significantly affects the level of domestic investment, rather than promoting any particular type of financial structure, focus should be upon the implementation of such the policies that ensure the efficiency of financial intermediation. Third as the ARDL short-run coefficients show that the effectiveness of financial sector development in raising the level of investment is limited to the short run only and less robust in the long run.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…First, as suggested by Ndikumana (2003), it is better to think in terms of banks and stock market rather than bank vs stock market because both types of indicators affect the level of domestic investment. Second in line with the findings of Raheem and Oyinlola (2017) and Iheonu et al (2020), as the efficiency-based, bank-based and market-based, financial development indicator significantly affects the level of domestic investment, rather than promoting any particular type of financial structure, focus should be upon the implementation of such the policies that ensure the efficiency of financial intermediation. Third as the ARDL short-run coefficients show that the effectiveness of financial sector development in raising the level of investment is limited to the short run only and less robust in the long run.…”
Section: Discussionmentioning
confidence: 86%
“…Further, examining the relationship between financial development and investment in three countries of South Africa, namely, Botswana, South Africa and Mauritius, during 1976–2014 with the help of ARDL bounds test approach and flexible accelerator model, the author (Muyambiri, 2017) found positive short-run effect of both indicators (bank and market based) of financial development on investment in Botswana, negative effect of bank-based indicator in short run and positive effect of market-based indicator in long run in South Africa, while in context to Mauritius, the market-based indicators had a positive effect on investment only in the short run. Raheem and Oyinlola (2017) employ a system-GMM technique for 31 countries in sub-Saharan Africa during the period 1999–2010. This study finds that financial development plays an important role to mobilize savings for investment.…”
Section: Financial Development and Investmentmentioning
confidence: 99%
“…The choice of our variables was informed by previous studies such as Hermes and Lensink (2003), Alfaro et al (2004), Blonigen and Wang (2005), Mengistus and Adams (2007), Alleyne and Edwards (2011), Nguyen and To (2017), Raheem and Oyinlola (2013), Saidi et al (2022), and Ochi et al (2022). Economic growth is measured by annual rate of GDP per capita growth.…”
Section: Empirical Methodologymentioning
confidence: 99%
“…However, it was concluded that, even in the face of good governance, FDI has no positive impact on growth. Raheem and Oyinlola (2013) examined the impact of foreign direct investment and governance quality on economic growth in seven ECOWAS countries from 1996 to 2010. They used the threshold autoregressive (TAR) model to determine the optimal level of governance, which, once attained, will induce the positive impact of FDI on growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their study observed that private savings were positively and significantly influenced by financial development and real interest rates in the long run in Egypt. Using the Generalized Methods of Moments (GMM) and data from 1999 to 2010, Raheem and Oyinlola (2016) studied the interlinkages between financial development, savings and investment in 37 Sub-Saharan African (SSA) countries. The finding was that improved financial development helped in the mobilization of more savings, which in turn accelerated the investment capacity of SSA countries.…”
Section: Literature Reviewmentioning
confidence: 99%